Late Pleistocene/early Holocene maritime interaction in Southeastern Indonesia – Timor Leste. (December 2016) - Reepmeyer, Christian; O'Connor, Sue; Mahirta,; Maloney, Tim; Kealy, Shimona
Abstract: This study analysed over 1000 obsidian stone artefacts excavated from two adjoining shelters at Tron Bon Lei on Alor Island Indonesia using portable XRF. The study showed an unambiguous separation of three different source locations (Groups 1, 2 and 3). Two sources (Group 2 and 3a, b, c) dominate the assemblage numerically. Group 1 and 2 indicate use of a single volcanic formation with a strong match between Group 1 artefacts and artefacts from sites in Timor Leste. Obsidian occurs in the earliest occupation layer in the Alor sites but does not include Group 1 artefacts which occur only after approx. 12, 000 cal BP. Currently the geographical location of the Group 1 outcrop is unknown, however, based on the late appearance of the Group 1 artefacts in the Alor sequence it is likely that the location is not on Alor, but rather on another island of the Sunda chain. The dating of Group 1 artefacts in widely spaced sites on the never geographically connected islands of Timor and Alor indicates that maritime interaction between islands began by at least the terminal Pleistocene. The distribution of the obsidian in Tron Bon Lei shelter Pit B shows that there were periods of more intense interaction punctuated by periods when interaction declined or ceased. Highlights: Largest geochemical study of obsidian artefacts in Island Southeast Asia. Analysis of obsidian distribution in an undisturbed rockshelter sequence, starting from 20, 000 cal BP. Geochemical analysis of a minimum of three new obsidian sources. Identification of maritime raw material transportation starting in the terminal Pleistocene. The assemblage shows that lithic and food consumption follow different patterns.